2009
DOI: 10.1007/s00701-009-0448-5
|View full text |Cite
|
Sign up to set email alerts
|

Ciliated craniopharyngioma—case report and pathological study

Abstract: The clinical course for this case is discussed together with a review of the pathological literature for ciliated craniopharyngioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Interestingly, strips of FOXJ1 positive motile ciliated columnar epithelium reminiscent of Rathke’s cleft cyst epithelium were also present in these two papillary craniopharyngioma cases (Figure 5f ) . These two cases presumably represent “ciliated craniopharyngiomas,” that have been reported, but only rarely (44). Notably, these two “ciliated craniopharyngioma” cases were both, as would be expected for papillary craniopharyngioma, positive for BRAF V600E by genotyping and immunohistochemistry (Supplemental figure 3).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Interestingly, strips of FOXJ1 positive motile ciliated columnar epithelium reminiscent of Rathke’s cleft cyst epithelium were also present in these two papillary craniopharyngioma cases (Figure 5f ) . These two cases presumably represent “ciliated craniopharyngiomas,” that have been reported, but only rarely (44). Notably, these two “ciliated craniopharyngioma” cases were both, as would be expected for papillary craniopharyngioma, positive for BRAF V600E by genotyping and immunohistochemistry (Supplemental figure 3).…”
Section: Resultsmentioning
confidence: 95%
“…Previous studies have infrequently reported the identification of “ciliated papillary craniopharyngioma” with apical tufts of cilia on neoplastic epithelium (44). We observed two such cases in our cohort, and demonstrated that cells at the apical surface of the neoplastic squamous epithelium stain positively for FOXJ1 and ARL13B.…”
Section: Discussionmentioning
confidence: 99%
“…30,34,68,77,78 As these rare lesions' epithelial cells undergo transformation and no longer exhibit ciliation, it has been proposed that they develop into the more characteristic stratified squamous cell epithelial cells traditionally observed in the squamouspapillary subtype of CP. 30,79 Finally, several cases of ciliated squamous-papillary CPs have been reported to arise directly from preexisting RCCs. 79,82,93 In one of these studies, Park et al 82 reported a case of an RCC with negative β-catenin accumulation that transitioned into a CP with positive β-catenin accumulation.…”
mentioning
confidence: 99%
“…30,79 Finally, several cases of ciliated squamous-papillary CPs have been reported to arise directly from preexisting RCCs. 79,82,93 In one of these studies, Park et al 82 reported a case of an RCC with negative β-catenin accumulation that transitioned into a CP with positive β-catenin accumulation. 82 A major limitation of these reports, however, is that for any given case it cannot been proven with certainty that a CP neoplasm actually arose from a preexisting RCC.…”
mentioning
confidence: 99%
“…35 In the clinical setting, differentiation of craniopharyngioma and Rathke cleft cyst with squamous metaplasia is not always feasible. Currently, it is debated whether ciliated craniopharyngioma represents a transitional stage between craniopharyngioma and Rathke cleft cyst, 36 or is a distinct subtype of craniopharyngioma. Recently, Coy et al demonstrated two cases of ciliated craniopharyngioma with positive VE-1 immunostaining that showed FOXJ 1 expression.…”
Section: Discussionmentioning
confidence: 99%